SII@EDU social innovation initiatives: educational mural for pre-school at Sekolah Kebangsaan Raja Muda (SBT) (SKRM) / Roslaili Anuar - Anuar, Roslaili (Galeri Seni Tuanku Nur Zahirah (GESTURZ), Universiti Teknologi MARA in collaboration with Faculty of Education (EDU), Universiti Teknologi MARA, Shah Alam, 2020)
In collaboration with Sekolah Kebangsaan Raja Muda (SBT), the Educational Mural project for Pre-School, themed the Jungle, was conducted.